The Legal Policy of Regulating the Concept of Future Value Amid the Discourse on State Finances in State-Owned Enterprises - Dewi Lestari Djalal (Global Legal Review, 2021)
The status of state finance is related to the legal consequences which occur and must be borne by the parties. The legal position of state finances will also determine any loss of the state finances which occur as a result of a business decision made by SOE. Business decision made by the Board of Directors of a company has significant impacts on the performance of a Limited Liability Company (LLC) such as revenue and increased value of the company. In order to generate profit, the Board of Directors must be able to take appropriate corporate action. The Board of Directors of LLC often takes future value action by performing risky action which may damage the company in expectation of the highest possible profit for the company in the future. In the context of SOE management is often viewed as detrimental to state finances because it’s considered corporate crime which ends with corruption. Problems occur when performing assessment of state loss as SOE and Law Enforcers have different perspectives. Law Enforcers often can’t see the future value of a corporate action taken by an SOE Persero. The problem in this paper is what is the Legal Policy of Regulating the Concept of Future Value in Determining State Financial Loss? The research method was judicial normative, which is a study that emphasizes the usage of written legal norms which are related to the source’s perception and view. The research result showed that policy related with future value transaction performed by the Board of Directors of SOE (LLC) incorporate action for the future interest of the company should be viewed as an action by the Board of Directors of SOE to realize the vision and mission of SOE, not as state financial loss if the value of the business loss is smaller than the profit generated by SOE and doesn’t affect state capital (state assets) which is deposited to SOE.